Pengaruh Intensitas Modal, Leverage, Manajemen Laba, dan Ukuran Perusahaan Terhadap Tax Avoidance - Safira Almira Yasmin; Prita Andini (Jurnal Mutiara Ilmu Akuntansi, 2024)
This study aims to determine the influence of Capital Intensity, Leverage, Earnings Management and Company Size on Tax Avoidance. The sample selection technique in this study uses purposive sampling and obtained 40 companies in the food and beverage sub-sector that are listed on the Indonesia Stock Exchange for the 2019-2022 period. The data analysis used in this study is multiple linear regression using SPSS version 26 software. Based on the results of the study, it can be concluded that Capital Intensity has an effect on Tax Avoidance, while Leverage, Earnings Management and Company Size do not have a significant effect on Tax Avoidance.